Photolysis of dicamba (3,6-dichloro-2-methoxybenzoic acid) in aqueous solution and dispersed on solid supports - Jean-Pierre Aguer; Frédéric Blachère; Pierre Boule; Sandrine Garaudee; Chantal Guillard (International Journal of Photoenergy)
Dicamba (3,6-dichloro-2-methoxybenzoic acid) was exposed to UV light in aqueous solution. It was also irradiated in the solid phase without support or adsorbed on laponite (a synthetic clay) and ferric oxide.